Interventions to Support System-level Implementation of Health Promoting Schools: A Scoping Review - McIsaac, Jessie-Lee D. (Int J Environ Res Public Health, 2016)
Health promoting schools (HPS) is recognized globally as a multifaceted approach that can support health behaviours. There is increasing clarity around factors that influence HPS at a school level but limited synthesized knowledge on the broader system-level elements that may impact local implementation barriers and support uptake of a HPS approach. This study comprised a scoping review to identify, summarise and disseminate the range of research to support the uptake of a HPS approach across school systems. Two reviewers screened and extracted data according to inclusion/exclusion criteria. Relevant studies were identified using a multi-phased approach including searching electronic bibliographic databases of peer reviewed literature, hand-searching reference lists and article recommendations from experts. In total, 41 articles met the inclusion criteria for the review, representing studies across nine international school systems. Overall, studies described policies that provided high-level direction and resources within school jurisdictions to support implementation of a HPS approach. Various multifaceted organizational and professional interventions were identified, including strategies to enable and restructure school environments through education, training, modelling and incentives. A systematic realist review of the literature may be warranted to identify the types of intervention that work best for whom, in what circumstance to create healthier schools and students.